Elevated Ammonia Level as a Diagnostic Marker of Hepatic Encephalopathy - Ochirkhuree, Bayarmaa; Namdag, Bira; Jambal, Sarangerel; Gunchin, Batbaatar (Central Asian Journal of Medical Sciences, 2016)
Objectives: Hepatic encephalopathy (HE) is a common and prognostic complication of cirrhosis. It may reflect either a reversible metabolic encephalopathy, brain atrophy, edema or any combination of these conditions. The mechanisms causing brain dysfunction in liver failure are still unknown. Ammonia is the best-characterized neurotoxin that precipitates HE. The purpose of this study was to ascertain the role of ammonia in HE. Methods: A hospital-based prospective study on HE was carried out at the First Central Hospital of Mongolia and the Chingeltei-Uul District Hospital in 2011-2013. Patients with hepatic failure were subdivided into the three following groups: (1) patients without HE, (2) patients with grade l-ll HE, (3) patients with grade lll-IV HE. We took liver function tests, Model for End-Stage Liver Disease (MELD) score and blood ammonia and correlated them with the severity of encephalopathy. The mean variables ±SD, p-values, and Pearson coefficients were calculated by SPSS 17.0. Results: The total sample size was 120 and the mean age was 36.8 ±15.4 years. Elevated ammonia level was observed in every stage of HE and increased by stage (p< 0.0001) MELD score and elevated ammonia level had a strong positive correlation (r = 0.54, p = 0.0001). In patients with any infection, the ammonia level was higher (p< 0.0001) than other groups. Conclusion: Ammonia is one of the diagnostic biomarkers of HE.